Cloning and expression of an elongation factor-1α in sea bream ( Sparus aurata ) larvae and adult tissue - Nowell, M. A. (2014)
A clone encoding the polypeptide elongation factor EF-1a was isolated from a complementary DNA library prepared from sea bream (Spartus aurata) larvae 1 to 10 days after hatching. The deduced amino acid sequence is between 82% and 95% similar to EF-1a in other animal species. EF-1a messenger RNA is present at low abundance in sea bream embryos prior to gastrulation, but at around 15 hours postfertilization, there is a 10-fold increase in transcript levels. This increase presumably reflects midblastula transition in this species. In adult sea bream, EF-1a appeared to have a relatively uniform distribution across all the tissues analyzed.